2016
DOI: 10.1177/1468087416643901
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation of turbulent, cavitating fuel flow inside a 9-hole Diesel injector including needle movement

Abstract: We investigate the turbulent multiphase flow inside a nine-hole common rail Diesel injector during a full injection cycle of ISO 4113 diesel fuel into air by implicit large-eddy simulation (LES). The simulation includes a prescribed needle movement obtained from a one-dimensional multi-domain simulation. The injector geometry is represented by a conservative cut-element-based immersed boundary method with subcell resolution, which has been developed for the application in the context of cavitating liquid flows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 60 publications
1
43
0
Order By: Relevance
“…Similar conclusions about the effect of the fuel properties have already been seen both experimentally and numerically for other kinds of biodiesel [27]- [31] and for winter fuel formulations [32]- [34]. Recently, a few authors [35]- [39] have showed that it is important to consider not only the changes in the fuel properties related to the fuel composition, but also those related to the different temperature and pressure conditions along the nozzle geometry, which are traditionally neglected.…”
supporting
confidence: 72%
“…Similar conclusions about the effect of the fuel properties have already been seen both experimentally and numerically for other kinds of biodiesel [27]- [31] and for winter fuel formulations [32]- [34]. Recently, a few authors [35]- [39] have showed that it is important to consider not only the changes in the fuel properties related to the fuel composition, but also those related to the different temperature and pressure conditions along the nozzle geometry, which are traditionally neglected.…”
supporting
confidence: 72%
“…The needle lift profile was however approximated as linear in both the start and end of injection. In [4] a density-based solver with a cavitation model based on thermodynamic equilibrium and LES assumptions was applied to the main injection of a 9-hole injector with a realistic needle-lift profile. Two different designs of an injector showing erosive cavitation were instead simulated in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Results are presented for a micro-channel flow, as well as for a real injector case. Another cavitating injector simulation was presented by Örley et al in [12], where a density-based solver with explicit time integration and the single-fluid approach were applied. Pressure peak intensities in the order of 1000 [bar] were recorded in both works.…”
Section: Introductionmentioning
confidence: 99%